Toxicological Study Employing Repeated Doses of Garcinielliptone FC, a Polyisoprenylated-Benzophenone Isolated from Seed of Platonia Insignis Mart - Silva, Ana P. (2015)
The major constituent from the hexane extract of the seeds of P. insignis is GFC (garcinielliptone FC). Doses of 25, 50and 75 mg/kg of GFC were aseptically suspended in 0.05% Tween 80 dissolved in 0.9% saline (vehicle) and orally administered for30, 90 and 120 consecutive days to adult Swiss mice. In this work, the repeated oral administration, in animals of both sexes,demonstrates that this compound is not able to induce mortality and/or behavioral changes in adult mice. In addition, body weightgain, feed intake and disposal of excreta were not altered by the administration of this compound with repeated doses. Furthermore,no differences in weight and macroscopic structure of the brain, liver, kidney, lung, heart and spleen between groups of male andfemale adult mice were observed after treatment. During the periods of treatment, GFC produced no significant changes onhaematological and biochemical parameters in male and female mice treated with all doses used. The aim of this study was toinvestigate the toxicological potential of GFC through behavioral, hematological, biochemical and morphological parameters inanimals in order to ensure the safe use of Platonia insignis in folk medicine.